EUROPEAN PLASTIC ART IN ANTHROPOLOGICAL DIMENSION: FROM THE CLASSICS TO THE POSTMODERNISM - R. M. Rusin; I. V. Liashenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is devoted to the analysis of corporality as an attribute of plastic art in the Ancient art, the Middle Ages, the Renaissance, the modernism and the postmodernism. Theoretical basis. The authors consider historical development of the art as a change of paradigms. Within each paradigm a special understanding of art is created, which is characterized both by the act of creativity itself and by the evaluation of its results. Particularly urgent is the task to identify the origins of these changes, to indicate their stages, the direction of the evolution of artistic creativity. In this context, corporality as a paradigm of European plastic art is considered in the article in the concrete historical dimension from the classics to the postmodernism. Originality. Postmodern experiments stimulate blurring the borders between the traditional forms and genres of art. Review of canonical ideas about the creation and destruction, order and chaos in art illustrates conscious reorientation from the classical understanding of artistic creativity to the construction of artifacts-simulacra, which is a characteristic feature in the oeuvre of contemporary artists, ranging from the pop art to the present day. Conclusions. The ideas of postmodern philosophers found their visual embodiment in modern artistic practices. Reconstruction of the body, re-switching of its elements according to the principle of chaotic collage, the interpretation of the human body as a separate substance isolated from the individual him/herself, which is presented as a phenomenon of mass culture, became the basis of the creative method of contemporary plastic art. The ideas of postmodern philosophers have found their visual embodiment in the contemporary artistic practices.